2016
DOI: 10.1159/000448054
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal Inflammation, Infections and Mental Disorders

Abstract: Background: The objective of this descriptive review is to summarize the current scientific evidence on the effect of prenatal exposure to maternal infection and immune response on the offspring's risk for mental disorders (schizophrenia spectrum disorders, autism spectrum disorders, attention-deficit hyperactivity disorder, anorexia nervosa, and mood disorders). Sampling and Methods: Studies were searched from PubMed and Ovid MEDLINE (R) databases with the following keywords: ‘prenatal exposure delayed effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
43
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(45 citation statements)
references
References 110 publications
(295 reference statements)
1
43
0
1
Order By: Relevance
“…For instance, in urinary tract infections, bacteria/virus could directly reach the fetus or the baby when descending the vaginal canal. On the other hand, epidemiological studies support the association between prenatal exposure to various infectious pathogens and psychiatric disorders, suggesting that general immune activation (e.g., elevated cytokine levels) rather than the type of pathogen may be a common underlying pathway increasing the risk for mental disorders (Flinkkilä, Keski‐Rahkonen, Marttunen, & Raevuori, ; Scola & Duong, ).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, in urinary tract infections, bacteria/virus could directly reach the fetus or the baby when descending the vaginal canal. On the other hand, epidemiological studies support the association between prenatal exposure to various infectious pathogens and psychiatric disorders, suggesting that general immune activation (e.g., elevated cytokine levels) rather than the type of pathogen may be a common underlying pathway increasing the risk for mental disorders (Flinkkilä, Keski‐Rahkonen, Marttunen, & Raevuori, ; Scola & Duong, ).…”
Section: Discussionmentioning
confidence: 99%
“…Exaggerated maternal inflammation during pregnancy is usually associated with poor trophoblastic invasion, placental malperfusion and IUGR (Anton, Brown, Parry, & Elovitz, ; Robb, Cotechini, Allaire, Sperou, & Graham, ). It is also linked to neurodevelopmental disorders in the child (Angelidou et al, ; Brown, ; Flinkkilä, Keski‐Rahkonen, Marttunen, & Raevuori, ). Lipopolysaccharide (LPS) is an endotoxin that triggers systemic and local inflammatory response (Cotechini et al, ).…”
Section: Models Of Iugr and Fetal Programmingmentioning
confidence: 99%
“…A connection between schizophrenia and inflammation is emerging in the literature, supported by many research approaches. 1,2 Research also supports the idea that individual risk for schizophrenia is increased with prenatal infection exposure, 3 and that a genetic contribution may also increase vulnerability to prenatal infection. 4 Imaging studies have found increased microglia activation binding in people with schizophrenia, [5][6][7] and genome-wide association studies have linked schizophrenia to the major histocompatibility locus.…”
Section: Introductionmentioning
confidence: 78%